Reality pedagogy across contexts : comparing learning environments in the Bronx (New York) and Dresden (Germany) - Sirrakos, Georgeos (Curtin University, 2012)
The work presented in this thesis was a response to my observations of differences in learning environments and student attitudes toward science between the Bronx, New York and Dresden, Germany when I was a teacher in these locations. In this thesis, I present reality pedagogy as an approach to teaching that allows students from all backgrounds to be successful in science. Reality pedagogy acknowledges the significance of using cultural referents from student experiences as key points from which pedagogy is enacted. Further, reality pedagogy is meant to provide students with classroom agency by including students in the teaching and learning process.This study used a mixed-methods exploratory approach to investigate the outcomes of reality pedagogy in terms of changes in students’ perceptions of the learning environment and their attitudes toward science. The Questionnaire Assessing the Learning Environment and Student Attitudes (QuALESA) was administered to 142 students in grades 8–10 at Bronx High School in New York City and the International School of Dresden in Dresden, Germany. The QuALESA was created by combining learning environment scales from the Constructivist Learning Environment Survey (CLES) and the What Is Happening In this Class? (WIHIC) questionnaire with attitude scales from the Test of Science-Related Attitudes (TOSRA). In addition, qualitative data were collected from cogenerative dialogues, classroom observations, and semi-structured student interviews and were used to support findings from the QuALESA.Because one of the aims of the study was to establish the validity and reliability of the QuALESA, it was administered at the beginning and conclusion of the 2010–2011 academic year in two high school science classrooms in the Bronx and five high school science classrooms in Dresden. Data analyses supported the factorial validity and reliability of the QuALESA for use with these samples.Overall changes in student perceptions of the learning environment and attitudes toward science in response to reality pedagogy were also investigated. MANOVA revealed significant improvements between pretest and posttest for six of the seven scales (Involvement, Cooperation, Personal Relevance, Critical Voice, Shared Control, and Enjoyment of Science Lessons). Classroom observations supported the changes revealed by the quantitative data analyses and showed shifts in teaching practices aimed at more involvement of students in the teaching and learning of science. However, when differences between how reality pedagogy manifested itself in classroom in the Bronx and Dresden were also explored in terms of student learning environment perceptions and attitudes toward science, it was found that students in Dresden had significantly higher pretest scores for six scales on the QuALESA. However, these pretest differences between the two locations were no longer present by the time of the posttest.While the quantitative data indicated that, over time, the perceptions and attitudes of students from the Bronx became more closely aligned with those of students from Dresden, the qualitative data revealed differences in how reality pedagogy was enacted in each geographic area. Students in the Bronx focused more on changing teacher practices to engage students more in science, whereas students in Dresden were more concerned with increasing their roles as co-teachers and sharing control with the teacher.Finally, when the quantitative data were analyzed to explore associations between students’ perceptions of their learning environment and their attitudes toward science, positive and statistically significant associations emerged between several learning environment scales and the attitude scales.Overall, the findings of this study add to the body of evidence concerning the effectiveness of employing reality pedagogy as a pedagogical approach to teach science across a variety of contexts.